The natural compound neobractatin inhibits cell proliferation mainly by regulating the RNA binding protein CELF6. Issue 4 (28th January 2022) - Zheng, ZhaoQing; Tan, JiaQi; Zhang, Juan; Wu, Man; Chen, Gan; Li, Zhuo; Shi, XiaoQin; Fu, WenWei; Zhou, Hua; Lao, YuanZhi; Zhang, Li; Xu, HongXi
Abstract : CELF6 acts as a tumor suppressor and a novel therapeutic target in cervical cancer. NBT upregulated CELF6 expression in vitro and in vivo to inhibit the cancer cell growth. Abstract : The fruits of Garcinia bracteata can be eaten raw or processed into spices, which are considered to possess nutritional and medicinal value. Neobractatin (NBT) is a natural compound isolated from Garcinia bracteate . This study showed that NBT showed antitumor effect by upregulation of CELF6. CELF6, an RNA-binding protein of the CELF family, is involved in cancer cell proliferation. However, the role of CELF6 in human cervical cancer remains unknown. Here, we showed that CELF6 overexpression significantly suppressed HeLa cell proliferation. Mechanistically, the RNA immunoprecipitation sequencing (RIP-seq) results suggested that CELF6 physically targeted the cyclin D1 transcript, affecting protein stability. Overexpression of CELF6 increased the degradation of cyclin D1. Consistent results were obtained for the effect of NBT, which increased the expression of CELF6 at both the mRNA and protein levels. An in vivo study further confirmed the regulatory effect of NBT on CELF6 and cyclin D1 levels in a HeLa xenograft model. Similar effects of NBT on CELF6 were also shown in K562 cells in vitro and in vivo . In conclusion, our findings identified CELF6 as a tumor suppressor and a novel therapeutic target in cervical cancer. The upregulation of CELF6 expression by NBT and its antiproliferative effect on HeLa cells indicated that NBT from G. bracteata might be a small-molecule compound targeting CELF6.